The Effect of Environmental and Bio-Accounting on Food System Resilience with Sustainable Business Moderating Variable - Hardianto, Ade Manggala; Sidharta, Eka Ananta; Novitasari, Yuli; Kurnia, Liyanita Dewi; Antovi, Muhamad Zacky; Lita, Rossa; Putri, Zahra Annisa (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines how environmental and bio-accounting strengthen livestock governance to enhance food system resilience and sustainable business practices. Research Methodology: This study employs a mixed-methods design, combining quantitative analysis and qualitative case studies in Kabupaten Bekasi, Indonesia, a strategic livestock production area facing environmental and governance challenges. Environmental accounting integrates environmental costs and performance indicators into organizational decision-making, whereas bio-accounting values biological assets based on their ecological contributions and impacts. Results: This study makes a novel contribution by reconceptualizing environmental and bio-accounting practices. The findings indicate that integrating environmental and bio-accounting improves transparency, accountability, and sustainability-oriented management. These mechanisms enhance resource efficiency, support informed decision-making, and strengthen the resilience of livestock-based food systems. Conclusions: This study confirms that integrating environmental and bio-accounting practices strengthens governance capacity and promotes adaptive management aligned with sustainable business principles and long-term value creation. Limitations: This study focused on a single regional case, which may limit its generalizability. Future research should expand coverage across regions and apply longitudinal approaches to examine the long-term impacts. Contributions: This study contributes to sustainability accounting literature and provides practical insights for policymakers and managers implementing Environmental, Social, And Governance (ESG)-oriented livestock governance strategies.